The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5935/1806-0013.20150004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pain at the head, face and neck and its association with quality of life in general population of Piracicaba city, Sao Paulo: an epidemiological study

Abstract: BACKGROUND AND OBJECTIVES:Head, face and neck pain affects a large portion of the world population, however there are few studies reporting this condition in general Brazilian population. This study aimed at investigating the prevalence of head, face and neck pain and its impact on the quality of life of adults of Piracicaba city, São Paulo. METHODS:The sample was made up of 400 volunteers of both genders, aged between 20 and 50 years, who were randomly approached in six crossing points of the city. Socio-demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…T he f i ndi ngs of t h is st udy i ndicate t he administration of PA associated with codeine reduces the orofacial nociceptive response induced by formalin, capsaicin, and glutamate, which are recognized as relevant substances for the study of new antinociceptive drugs. 24 Although some studies have shown antinociceptive effect of PA or essential oils with high concentrations of this molecule, 25,26 this is the first study to report orofacial antinociceptive activity for the association of PA with codeine, a drug used to treat orofacial pain, especially in acute situations. The proposed association of PA with codeine aims to make it possible to decrease the amount of opioid analgesic administered, minimizing possible undesirable effects.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…T he f i ndi ngs of t h is st udy i ndicate t he administration of PA associated with codeine reduces the orofacial nociceptive response induced by formalin, capsaicin, and glutamate, which are recognized as relevant substances for the study of new antinociceptive drugs. 24 Although some studies have shown antinociceptive effect of PA or essential oils with high concentrations of this molecule, 25,26 this is the first study to report orofacial antinociceptive activity for the association of PA with codeine, a drug used to treat orofacial pain, especially in acute situations. The proposed association of PA with codeine aims to make it possible to decrease the amount of opioid analgesic administered, minimizing possible undesirable effects.…”
Section: Discussionmentioning
confidence: 89%
“…32 PA alone and associated with codeine reduced orofacial nociception induced by capsaicin, but the drug combination did not show synergistic activity, which is observed when the effect promoted by a drug combination is superior to the activity promoted by isolated substances. 24 Capsaicin-induced nociception involved the participation of TRPV1. 33 This information supports the finding obtained in the docking analysis, which showed affinity of PA for this receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the selected theme, it is possible to note the practical relevance, since pain of dental origin interferes in the quality of life of the patients, since it causes social and professional damages such as sleep disturbances, physical and emotional fatigue, loss of social contact, food, limitation of daily activities, and absenteeism at work 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic pain has been demonstrated to influence the quality of life as it can disturb sleep and lead to physical and emotional fatigue, loss of social contacts, difficulty in performing activities of daily living, and absenteeism [17]. Patients with CNP show impaired quality of life, which affects not only physical but also mental health [18,19].…”
Section: Introductionmentioning
confidence: 99%